2016
DOI: 10.21082/jbio.v4n1.2008.p35-40
|View full text |Cite
|
Sign up to set email alerts
|

ULASAN Kajian Filogenetika Molekuler dan Peranannya dalam Menyediakan Informasi Dasar untuk Meningkatkan Kualitas Sumber Genetik Anggrek

Abstract: Molecular Phylogenetic Studies in Providing BasicKnowledge to Improve Quality of Genetic Resources of Orchid. Topik Hidayat and Adi Pancoro. Early information resulted from molecular phylogenetic studies of many important ornamental crops is often less attention to many growers and farmers. Phylogenetics is one of the most preferable method in systematics to reconstruct evolutionary relationships of groups of biological organisms in order to understand their biodiversities. This has been revolutionized by DNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
9

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 0 publications
0
14
0
9
Order By: Relevance
“…Monotes katangensis (sequence from GeneBank database) is an outgroup because it has a distant relationship with Dipterocarpaceae research samples. According to Hidayat and Pancoro (2008), in the analysis of phylogenetics, outgroup lead to the polarization of characters or characteristics, namely apomorphic and plesiomorphic characters. Apomorphic characters are the changed and derived characters which were found in the ingroup (species which were studied), whereas the plesiomorphic character is the primitive character was found in the outgroup.…”
Section: Phylogenetic Tree Reconstruction Phylogenetic Analysis Of Rbmentioning
confidence: 99%
See 1 more Smart Citation
“…Monotes katangensis (sequence from GeneBank database) is an outgroup because it has a distant relationship with Dipterocarpaceae research samples. According to Hidayat and Pancoro (2008), in the analysis of phylogenetics, outgroup lead to the polarization of characters or characteristics, namely apomorphic and plesiomorphic characters. Apomorphic characters are the changed and derived characters which were found in the ingroup (species which were studied), whereas the plesiomorphic character is the primitive character was found in the outgroup.…”
Section: Phylogenetic Tree Reconstruction Phylogenetic Analysis Of Rbmentioning
confidence: 99%
“…Phylogenetic analysis is one of the most commonly used methods in systematic to understand the diversity of living things through reconstruction of relationship. Along with the rapid advancement of molecular biology, data of DNA have been used in many phylogenetic studies to get more accurate information (Hidayat and Pancoro 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Based on the clustering pattern suggested that Lansium and Aglaia is a monophyletic group that had a high similarity among the members. According to Hidayat and Pancoro (2008) in a phylogenetic approach, a group of organisms whose members have a lot of similarities of character is considered to have a very close relationship and estimated descended from a common ancestor.…”
Section: Discussionmentioning
confidence: 99%
“…Penggunaan sekuen DNA sangat penting karena dapat mengetahui perubahan basa nukleotida menurut waktu dan dapat memperkirakan kecepatan evolusi yang terjadi. Hal tersebut dapat direkonstruksi hubungan evolusi antara satu spesies dengan spesies lainnya (Hidayat & Pancoro, 2008). DNA kloroplas banyak digunakan untuk mengetahui hubungan kekerabatan antara spesies angiospermae dengan tanaman lainnya, namun memiliki tingkat evolusi yang rendah.…”
Section: Pendahuluanunclassified